Estudio de factibilidad para la creación de una empresa productora y comercializadora de aparatos para tratamientos de ortodoncia y ortopedia maxilar en Armenia - Quindío (2013)
The study of the state of the textile sector in the department of Quindío, performed to analyze the characteristics of their development in this region, demonstrated results from the shortcomings that plague the economy, even business opportunities of the industry in international scenarios and possible implementation measures for the resolution and improvement of the textile sector; the study articulated other research studies associated with initiatives of technological development, environmental protection, readjustments in public policies and prominent market projections for the inclusion of the activities of clothing in the next plans of departmental development.